1993
DOI: 10.1017/s0094837300012343
|View full text |Cite
|
Sign up to set email alerts
|

Decay and preservation of polychaetes: taphonomic thresholds in soft-bodied organisms

Abstract: A series of experiments was carried out to investigate the nature and controls (oxygen, microbial populations, agitation) on the degradation of soft tissues. Decay was monitored in terms of morphological change, weight loss, and change in chemical composition in the polychaete Nereis virens. Polychaetes include a range of tissue types of differing chemical composition and preservation potential: muscle, cuticle, setae, and jaws. Regardless of conditions, all the muscle had broken down and fluid loss through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 34 publications
5
168
0
1
Order By: Relevance
“…2 hours prior to burial. For Nereis (body length 125-250 mm, supplied by Seabait Ltd., Northumberland, UK), one series of specimens was killed by immersion in freshwater (with a potential for associated osmotic cell rupture) and a second by exposing their heads to a stream of hot water (see Briggs and Kear [1993]). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 hours prior to burial. For Nereis (body length 125-250 mm, supplied by Seabait Ltd., Northumberland, UK), one series of specimens was killed by immersion in freshwater (with a potential for associated osmotic cell rupture) and a second by exposing their heads to a stream of hot water (see Briggs and Kear [1993]). …”
Section: Methodsmentioning
confidence: 99%
“…The cleaned organic residues were dried, powdered, and chemically analyzed for (1) non-water-soluble protein, (2) chitin, (3) water-soluble protein, (4) carbohydrate, and (5) phospholipid, using the various hydrolysis and colorimetric techniques employed by Briggs and Kear (1993). As a result of the obscuring effects of the sediment it was not possible to document absolute amounts, so these data have been recorded as percentages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[51] The same decay experiments allowed the chevron-shaped structures in Conopiscius, a Carboniferous chordate, to be interpreted as myomeres rather than external scales, and also indicated that a decay-resistant cuticle was not necessarily present in Pikaia from the Burgess Shale. [51,55] Decay in seawater has now been monitored in a range of taxa in laboratory experiments (see Table S1, Supporting Information): anthozoans, [56] annelids, [48] chaetognaths, [57] priapulids, [18] onychophorans, [17] pterobranchs, [58] enteropneusts, [59] nonvertebrate chordates, [20] and cyclostomes. [60] Thus the sequence of character loss has been determined for taxa representing most clades of eumetazoans.…”
Section: Boxmentioning
confidence: 99%
“…Sufficient calcium and phosphate ions must be available and pH must drop in order for calcium phosphate to precipitate instead of calcium carbonate (i.e., the calcium carbonate/phosphate switch). [24] Such a decrease is a normal result of bacterial decay, [26,31,48] but phosphatization tends to favor the preservation of particular tissues and taxa. [81,83] Decay experiments have shown that phosphatization occurs on a laboratory time scale and is not necessarily restricted to a few unusual settings.…”
Section: Authigenic Mineralization Saves Tissues Apparently Doomed Tomentioning
confidence: 99%